Regional sports development framework based on local socio-cultural potential and demographics in Aceh, Indonesia - Nova, Andi; Acha, Basyarudin; Tantri, Afri; Maulana Fajar, Muhammad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2026)
This study aimed to develop a sports coaching framework based on local socio-cultural and demographic potential in Aceh, Indonesia. The study used the Richey & Klein design and development model with five stages: needs analysis, design, development and validation, implementation and evaluation, and revision and dissemination. A total of 360 respondents participated, including officials from the youth and sports office, sports practitioners, coaches, and athletes. The main findings of the study resulted in a new model of regional sports development framework which is a recommendation for regional sports coaching in Aceh Province to increase competitiveness at the national level and the contribution of athletes in the national team. This model can be adopted in other regions with similar characteristics, particularly in Indonesia. It offers a new contribution to the literature by emphasizing the role of local socio-cultural and demographic factors in regional sports development. The proposed sports coaching framework is flexible and can support future sports development, especially in developing countries that face challenges in competing in popular sports such as football. It encourages a shift in focus toward sports with higher potential for success in individual events, based on local socio-cultural and demographic contexts, thereby enhancing opportunities for international achievement.